Identification and Comparison of Factors Affecting the Enhancement of Educational and Research Productivity of Faculty Members in Islamic Azad Universities of Tehran - Sharifi, Faemeh; Sourani Yancheshmeh, Reza; Alizadeh, Saeed; Mosleh, Maryam; Jahed, Hossein Ali (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to identify and compare the factors influencing educational and research productivity among faculty members at Islamic Azad Universities in Tehran. Methods and Materials: The research employed a mixed-methods approach, combining quantitative and qualitative data collection. A total of 341 faculty members from Islamic Azad Universities in Tehran participated in the study. Data were collected through a structured questionnaire designed to measure educational and research productivity. The validity and reliability of the questionnaire were confirmed using Cronbach's alpha and expert feedback. The data were analyzed using descriptive statistics, exploratory factor analysis, Friedman’s test for ranking priorities, and multiple regression analysis to determine the factors influencing faculty productivity. Findings: The results showed that faculty members prioritize educational productivity over research productivity, with educational activities ranked as the highest priority. Factors such as institutional support, access to resources, professional ethics, and political behavior significantly impacted both educational and research productivity. However, high expectations from university leadership were not found to be a significant influence on productivity. The study also revealed that socio-demographic factors, particularly academic rank, played a role in shaping research output, with senior faculty members demonstrating higher research productivity. Conclusion: Faculty productivity, both educational and research, is influenced by a combination of institutional support, individual motivations, and socio-demographic characteristics. Universities must focus on providing sufficient resources, reducing teaching loads, and fostering an environment of collaboration to enhance faculty performance.